Ustekinumab affects myofibroblast metabolism to alleviate intestinal fibrosis by targeting KDELC1 in Crohn’s disease through multi-machine learning combined with single-cell sequencing analysis - Ma, Su; Kang, Yongming; Yang, Zhonglin; Ji, Xingyu; Chen, Rui; Sun, Xiaomei (Frontiers in Medicine, 2024)
Ustekinumab (UST), a biologic against interleukin (IL) -12/23, is commonly used to treat Crohn's disease (CD). Myofibroblast (MF), is known as one of the most important factors causing intestinal fibrosis, and the treatment of UST are reported to alleviate the intestinal fibrosis. However, the genetic mechanism of UST treatment toward Crohn's disease is still unclear. Using the bioinformatics technology, this study analyzed the genes and potential pathways affected by UST in CD, and further explored the anti-fibrosis role, providing a new target for the treatment of CD. A total of 1341 DEGs associated with CD were selected through the analysis. Among them, 738 genes in healthy population display expression in low lever, but expression in high level in patients with CD and reduced in expression after the treatment of UST. By contrast, the expression of 603 genes exhibit high level, while low expression in CD and the expression are elevated after the treatment of UST. The results of function and pathway analysis showed that DEGs was mainly concentrated in response to foreign biological stimuli and bacterial-derived molecules. DEGs is mainly enriched in chemokines, TNF, IL-17 and other signaling pathways. Seven key genes, including NCRNA00236, LOC730101, ORP3, XG, UBFD1, KDELC1, RBP7, were identified. By single cell analysis, KDELC1 was closely related to MF activity. MF with high expression of KDELC1 is significantly enriched in promoting the biological function, signaling pathway and metabolism of fibrosis. The UST treatment was helpful to maintain the integrity of intestinal tissue structure, and UST treatment reduced the expression levels of collagen I and KDELC1 and the degree of intestinal fibrosis. MF with high expression of KDELC1 is closely related to the pathway that promotes fibrosis progression (TGF-β, epithelial mesenchymal transformation, TNF/NF-kB) and related metabolism (vitamin B6, arginine). Finally, the experiment showed that UST treatment was helpful to maintain the integrity of intestinal tissue structure, and reduced the expression levels of type I collagen and KDELC1 and the degree of intestinal fibrosis. KDELC1 regulates multiple biological functions including signaling pathways of MF. UST alleviates intestinal fibrosis by targeting KDELC1 to affect intramuscular fat metabolism and intercellular communication.